2018
DOI: 10.1016/j.jsxm.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Adenosine Receptors in the Myofibroblast Transformation in Peyronie’s Disease

Abstract: The effect of an ADORA2B agonist on TGF-β1-induced myofibroblast transformation shows a novel potential therapeutic target for PD if applied during early, non-stable phase of PD. Mateus M, Ilg MM, Stebbeds WJ, et al. Understanding the Role of Adenosine Receptors in the Myofibroblast Transformation in Peyronie's Disease. J Sex Med 2018;15:947-957.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…Notably the serum levels of TGF-β1 were similar in all groups irrespective of the perioperative approach after treatment with 8-SPT or 5-HD, suggesting the involvement of both signaling pathways in the release of TGF-β1. Previous studies have linked the adenosine signaling with TGF-β1 status in different contexts 57,58 ; however, further research is needed in order to clarify the relative contribution of mitochondrial KATP channel activity and the different types of adenosine-adenosine receptor in the induction of TGF-β1 in the particular setting.…”
Section: Discussionmentioning
confidence: 99%
“…Notably the serum levels of TGF-β1 were similar in all groups irrespective of the perioperative approach after treatment with 8-SPT or 5-HD, suggesting the involvement of both signaling pathways in the release of TGF-β1. Previous studies have linked the adenosine signaling with TGF-β1 status in different contexts 57,58 ; however, further research is needed in order to clarify the relative contribution of mitochondrial KATP channel activity and the different types of adenosine-adenosine receptor in the induction of TGF-β1 in the particular setting.…”
Section: Discussionmentioning
confidence: 99%
“…Mateus et al showed that among the four knowns adenosine receptors, ADORA1 and ADORA2B are significantly more prevalent in cells derived from PD plaque than non-PD TA tissues. 88 , 89 …”
Section: Introductionmentioning
confidence: 99%
“…Loughborough, United Kingdom) as described previously [16]. The tissue pieces were incubated in DMEM-F12 (GIBCO, Invitrogen,…”
mentioning
confidence: 99%